Memory and Securitization in Contemporary Europe (Palgrave Macmillan UK, 2018)
The volume is the first study to explore the intersection of memory and securitisation in the European context. By analysing a variety of practices ranging from film to art and new media, the book expands the existing theoretical framework of securitisation. The authors consider memory as a precondition for contemporary integration projects such as the European Union, and also showcase how memory is used to stage international conflicts. Following this memory-securitisation nexus, the European Union, and Europe more generally, emerges as an on-going cultural, political and social project. The book also examines developments outside the EU such as the conflict in Ukraine and the creation of the Eurasian Economic Union, which, the authors argues, have a profound impact on Europe. From a consideration of historical contexts such as national referenda the discussion proceeds to media and film analysis, artistic practice and more transient phenomena such as climate change.